Palbociclib in breast cancer neoadjuvant setting - Cabral Duarte, Sílvia Alexandra; Silva Pádua de Azevedo, Daniela; Tomé Ribeiro Malheiro Sarmento, Teresa; Verónica Velho Sousa, Marta (Autopsy and Case Reports, 2021)
Cyclin-dependent kinase 4/6 inhibitors represent a major advance in breast cancer treatment, emerging as the standard of care of the initial treatment of hormone receptor-positive and HER2-negative metastatic breast cancer. Their activity in this subset of patients leads to interest in their use in the adjuvant and neoadjuvant settings. This case report presents a real-life case of cyclin-dependent kinase 4/6 inhibitors use in a patient initially considered to have stage IV luminal HER2-negative breast cancer with liver metastasis. The discrepancy of treatment response between the breast tumor and liver node led to a repetition of the liver biopsy, which revealed metastasis of a neuroendocrine tumor of unknown primary. The breast tumor showed a partial response, and the initial therapeutic strategy was then redefined for curative intent. While cyclin-dependent kinase 4/6 inhibitors are not yet approved for clinical practice in the neo / adjuvant treatment of hormone receptor-positive breast cancer, this case report portrays a successful example of its application in a neoadjuvant setting.